Initial seven coefficient estimates for a subclass of bi-starlike functions - Janani, T.; Yalçın, S. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 517.5 In the present article, a subclass of bi-starlike functions is studied and initial seven Taylor–Maclaurin coefficient estimates |a_2|, |a_3|, … , |a_7| for functions in the subclass of the function class Σ are obtained for the first time in the literature. Few new or known consequences of the results are also pointed out.